Association of TLR4 gene rs4986790 and rs4986791 polymorphisms with asthma susceptibility: meta-analysis and trial sequential analysis - Nan Guo; Haokun Tian; Tiangang Song; Yu Peng (Annals of Saudi Medicine, 2024)
BACKGROUND: The current understanding of the correlation between TLR4 gene (toll-like receptor 4) rs4986790 and rs4986791 polymorphisms and asthma susceptibility is inconclusive, with studies and populations yielding conflicting results. OBJECTIVES: Evaluate this relationship using meta-analysis and trial sequential analysis (TSA). PATIENTS AND METHODS: Databases were systematically queried for relevant articles from the establishment of the database to 19 June 2023 adhering to predefined inclusion and exclusion criteria. Two authors independently conducted screening, data extraction, and quality evaluation. Meta-analysis and TSA were carried out using RevMan 5.4, StataMP 17.0, and TSA 0.9.5.10 Beta, with α=0.05. Subgroup analyses were conducted based on racial demographics. A sensitivity analysis was conducted employing a one-by-one exclusion method. Publication bias was assessed using the Begg and Egger tests. MAIN OUTCOME MEASURES: Association of asthma susceptibility with TLR4 gene rs4986790 and rs4986791 polymorphisms. SAMPLE SIZE: 23 articles included 22 studies on the rs4986790 polymorphism and 11 studies on the rs4986791 polymorphism on the TLR4 gene. RESULTS: Out of 692 studies screened, 23 met the inclusion criteria. While the overall meta-analysis showed no significant association between the TLR4 rs4986790 polymorphism and asthma susceptibility, subgroup analysis revealed a significant link in the Caucasian population. A significant association was noted in the meta-analysis, particularly among Asian populations, on the rs4986791 polymorphism. The sensitivity analysis indicated that the meta-analysis results were relatively stable. Publication bias analysis revealed minimal influence from publication bias. However, TSA was underscored by the necessity for additional original studies to further validate specific outcomes. CONCLUSIONS: Our study underscores the ethnicity-specific impact on the relationship between TLR4 polymorphisms and asthma susceptibility. While the overall findings for rs4986790 were not significant, the association with the Caucasian population merits further investigation. Furthermore, rs4986791 demonstrated a significant correlation with asthma susceptibility, specifically among Asian populations. LIMITATIONS: Our study predominantly examined the rs4986790 and rs4986791 polymorphisms, overlooking the potential influence of other genetic variants within TLR4.